LA PROBLÉMATIQUE DE L’APPROVISIONNEMENT VIVRIER D’UNE VILLE SECONDAIRE DANS LE CADRE DES RELATIONS VILLE-CAMPAGNE EN PAYS ADIOUKROU : DABOU - Atta Koffi Lazare; Gogbe Téré; Moussoh André Armand (European Scientific Journal, ESJ, 2014)
The rapid rise in the urban population in Adioukrou land brings about many worries on the rural supply of regional capital, Dabou by its rural zone. This situation is such worrying due to a rural economy dominated by the exportation crops at expend of raw crops. In front of an increasing urban population one query about the real capacity of the rural zone to satisfy the urban need in raw crops. This study is a contribution to perfect knowledge of the crops supplying system of the city of Dabou in the context of cities and villages relationship. The incapacity of the back country to satisfy its crops needs, oblige the city of Dabou to keeprelationship with other regions, but above with the city of Abidjan for its crops supplying.